Pseudoaneurysm formation due to bioglue use in aortic valve surgery - (:unkn) unknown (AVES PRESS LTD, 2015)
Introduction of bioglue as surgical adhesive equipment shortens operation time, decreases the need for blood transfusion, and improves hemostasis. However, as all new developments, it is not free of complications. In this study, we present a report of aortic pseudoaneurysm formation due to bioglue use in aortic valve surgery.
Keywords: Aortic valve surgery; bioglue; chronic inflammation; pseudoaneurysm